Zingiber officinale Ethanolic Extract Attenuated Reserpine-Induced Depression-Like Condition and Associated Hippocampal Aberrations in Experimental Wistar Rats - Olanrewaju JA; Owolabi JO; Awodein IP; Enya JI; Adelodun ST; Olatunji SY; Fabiyi SO (Dove Medical Press, 2020)
John Afees Olanrewaju,1,2 Joshua Oladele Owolabi,1,3 Ifedamola Patience Awodein,1 Joseph Igbo Enya,2 Stephen Taiye Adelodun,1 Sunday Yinka Olatunji,1 Sunday Oluwaseyi Fabiyi1 1Department of Anatomy, Ben Carson School of Medicine, Babcock University, Ilishan-Remo, Ogun State, Nigeria; 2Department of Anatomy, Faculty of Basic Medical Sciences, University of Ilorin, Ilorin, Nigeria; 3Department of Anatomy, Division of Basic Medical Sciences, University of Global Health Equity, Butaro, RwandaCorrespondence: Joshua Oladele Owolabi Email jowolabi@ughe.orgBackground: Repeated and regimented treatment with reserpine causes depression-like condition characterized by persistent mood disorder, feelings of severe despondency and dejection, thus altering the hippocampal morphology. Our study compared a well-known antidepressant (fluoxetine), with the potential of Zingiber officinale to ameliorate reserpine-induced depression and the associated hippocampal cornu ammonis 1 (CA1) neuronal cell damage.Methods: Forty-eight male Wistar rats, weighing 130– 160 g, were randomly assigned to 6 groups (n=8), housed in plastic cages under natural light and dark cycles at room temperature with access to feed and water ad libitum. Group-A (control) received distilled water. Group-B and Group-C orally received 400 mg/kg of Zingiber officinale and 10 mg/kg of fluoxetine, respectively, for 7 days, while Group-D intraperitoneally received 0.2 mg/kg of reserpine for 14 days. Group-E and Group-F intraperitoneally received 0.2 mg/kg of reserpine for 14 days followed by 400 mg/kg of Zingiber officinale and 10 mg/kg of fluoxetine respectively for 7 days. All animals were sacrificed by cervical dislocation at the end of experiment, and the brains hippocampi were dissected, excised and processed for various analyses including histology [H&E], histochemistry of GFAP expression by astrocytes and specific gene expressions including p53 gene, glutathione reductase (GSR), glutathione peroxidase and catalase (CAT).Results: Reserpine significantly depleted the expression of P53 and glutathione reductase (GSR) genes while significantly increasing the expression of glutathione peroxidase 1 (GPx-1) gene (P≤ 0.05). Also, a marked increase in the expression of catalase (CAT) gene was observed. Furthermore, histoarchitecture (photomicrographs) of hippocampus CA1 region showed disruption in the arrangement of pyramidal neurons and alterations in their morphologies when animals were treated with reserpine (Group D). There was also accompanying increased astrocyte densities within the CA1 region following reserpine treatment. These features indicated deleterious effects of reserpine. Both Zingiber officinale and fluoxetine treatments ameliorated these effects.Conclusion: These findings showed structural and molecular alterations associated with reserpine-induced depression. Also, Zingiber officinale was effective to provide ameliorative and protective effects against the neurotoxic effects of reserpine in the hippocampus, making it a potential candidate for treating depression and its associated neurodegenerative diseases.Keywords: reserpine-induced depression, Zingiber officinale (ginger), neurotoxicity, hippocampus